Comportamento das concentrações séricas e urinárias de creatinina e uréia ao longo de uma periodização desenvolvida em futebolistas profissionais: Relações com a taxa de filtração glomerular - Da Silva, Adelino Sanchez Ramos [UNESP]; Santhiago, Vanessa [UNESP]; Papoti, Marcelo [UNESP]; Gobatto, Claudio Alexandre [UNESP] (My University, 2006)
The creatinine and urea responses have been extensively used to evaluate the physical training impact. Therefore, the purpose of this study was to investigate the behavior of serum and urinary creatinine and urea concentrations during a soccer training program. Eighteen Brazilian soccer players were evaluated at the beginning (T1), in the middle (T2) and at the end (T3) of a soccer training program. The athletes had their anthropometric characteristics, aerobic capacity and alactic anaerobic metabolism efficiency assessed. Besides the measurement of serum and urinary creatinine and urea concentrations, the athletes had their creatinine clearance evaluated by three different methods. While the first method was independent from the urinary volume, the others were dependent. Anova one-way test followed by Newman-Keuls and Pearson product-moment coefficient were used to verify the responses and correlations of the data to the soccer training program. A significance level of 5% was chosen. The soccer training program led to an increase in aerobic (p < 0.01) and alactic anaerobic (p < 0.01) performances, however, the urinary volume diminished along the experiment (p < 0.05). The serum (p < 0.05) and urinary (p < 0.01) creatinine concentrations presented an opposite behavior during the soccer training program, in addition, there were not observed significant correlations between this parameters in any period of the study. The creatinine clearance assessed by the three different methods decreased in response to the training (p < 0.05). Significant correlations for all methods were observed only in T1. However, the urinary volume dependent methods were statistically correlated in T2 and T3. According to results, it can concluded that the serum and urinary creatinine concentrations were sensible to the training program developed, but presented opposite behaviour. This probably occurred due the limitations of the urinary method to assay creatinine and urea.
Behavior of the creatinine and urea seric and urinary concentrations during a periodization developed in professional soccer players: Relations with the glomerular filtration rate
Keywords: Physical training; Renal function; Soccer players; Urinary volume